SARS‐CoV‐2 infection as a trigger of autoimmune response - Maria C. Sacchi; Stefania Tamiazzo; Paolo Stobbione; Lisa Agatea; Piera De Gaspari; Anna Stecca; Ernesto C. Lauritano; Annalisa Roveta; Renato Tozzoli; Roberto Guaschino; Ramona Bonometti (Wiley, 2021)
Abstract Currently, few evidences have shown the possible involvement of autoimmunity in patients affected by coronavirus disease 2019 (COVID‐19). In this study, we elucidate whether severe acute respiratory syndrome coronavirus disease 2 (SARS‐CoV‐2) stimulates autoantibody production and contributes to autoimmunity activation. We enrolled 40 adult patients (66.8 years mean age) admitted to Alessandria Hospital between March and April 2020. All the patients had a confirmed COVID‐19 diagnosis and no previously clinical record of autoimmune disease. Forty blood donors were analyzed for the same markers and considered as healthy controls. Our patients had high levels of common inflammatory markers, such as C reactive protein, lactate dehydrogenase, ferritin, and creatinine. Interleukin‐6 concentrations were also increased, supporting the major role of this interleukin during COVID‐19 infection. Lymphocyte numbers were generally lower compared with healthy individuals. All the patients were also screened for the most common autoantibodies. We found a significant prevalence of antinuclear antibodies, antineutrophil cytoplasmic antibodies, and ASCA immunoglobulin A antibodies. We observed that patients having a de novo autoimmune response had the worst acute viral disease prognosis and outcome. Our results sustain the hypothesis that COVID‐19 infection correlates with the autoimmunity markers. Our study might help clinicians to: (a) better understand the heterogeneity of this pathology and (b) correctly evaluate COVID‐19 clinical manifestations. Our data explained why drugs used to treat autoimmune diseases may also be useful for SARS‐CoV‐2 infection. In addition, we highly recommend checking patients with COVID‐19 for autoimmunity markers, mainly when deciding on whether to treat them with plasma transfer therapy. Study Highlights WHAT IS THE CURRENT KNOWLEDGE ON THE TOPIC? ☑ Recent data sustain the idea that autoimmune phenomena exist in patients with coronavirus disease 2019 (COVID‐19), but other investigations are necessary to define the possible link between severe acute respiratory syndrome coronavirus disease 2 (SARS‐CoV‐2) infection and autoimmune disease onset. WHAT QUESTION DID THIS STUDY ADDRESS? ☑ In this monocentric study, we demonstrated how SARS‐CoV‐2 infection could be associated with an autoimmune response and development of autoantibodies. WHAT DOES THIS STUDY ADD TO OUR KNOWLEDGE? ☑ Patients with COVID‐19 having an increased level of inflammatory markers and strong autoantibodies positivity (i.e., antinuclear antibodies and antineutrophil cytoplasmic antibodies) presented the worst clinical outcome. HOW MIGHT THIS CHANGE CLINICAL PHARMACOLOGY OR TRANSLATIONAL SCIENCE? ☑ These results suggest that the drugs normally used to treat autoimmune diseases should also be considered during SARS‐CoV‐2, improving public health. In addition, before starting a transfer plasma therapy, it is important to also evaluate the autoimmunity conditions of the patients with COVID‐19. Transferring antibodies or trying to neutralize them should be done with precaution. It is possible that the risk of developing or increasing the autoimmune response may enhance.